Oral Mucosa Malignant Melanoma: Clinical Features, Diagnosis, Treatment, and a Case Report - Tze-Ta Huang; Kai-Yuan Hsiao; Chiang-Shin Liu; Tung-Yiu Wong; Jehn-Shyun Huang; Ken-Chung Chen (Journal of Dental Problems and Solutions - Peertechz Publications, 2015)
Primary oral mucosa malignant melanoma is a rare and biologically aggressive neoplasm. It is estimated about 1~2% of all oral malignancies with the incidence increasing with age. The prognosis of oral mucosa malignant melanoma is poor with the five-year survival rate is approximately 15%. The diagnosis of oral melanoma is usually delayed because it is always asymptomatic at the beginning and it resembles the epulis, amalgam tattoo or other oral lesions. In addition, nearly a third of all oral melanoma are amelanotic and may lack a radial growth phase, which makes early and accurate diagnosis even difficult. Thus, regional and distant metastases happen more frequently. Surgery is the first choice of treatment, and clinically negative necklymph nodes with neck dissection or radiotherapy are also recommended because of the high risk of subclinical regional metastasis.  In this article, we reviewed the clinical features, diagnosis, treatment, and presented a 70 y/o male who suffered from an easily bleeding lesion over right posterior palatal mucosa and gingiva who presented at hospital for help. We performed biopsy which revealed a malignant melanoma. He received supraomohyoid neck lymph node dissection, partial maxillectomy, and was reconstructed with anterior lateral thigh free fascia cutaneous flap. After surgical treatment, the patient kept regular follow-ups. The treatment outcome was good and the patient recovered with full swallowing and phonation function.